Kajian Dokumen Kebijakan Kemenag RI tentang Kurikulum Merdeka di Madrasah Ibtidaiyah - Dwi Putri Aprilia Vavadlilah; Siti Ghurrotus Saniyah; Ummi Afiatun Jannah; Moh. Syafi’i; Ahmad Thoyyib Mas’udi (Pascasarjana Universitas Qomaruddin, 2025)
This article aims to analyze the official policy documents published by the Ministry of Religious Affairs of the Republic of Indonesia (Kemenag RI) regarding the implementation of the Merdeka Curriculum in Madrasah Ibtidaiyah. The study was conducted through a literature review approach to enrich the literature on Islamic education policy and provide a mapping of curriculum policy directions within the madrasian environment. The document review was conducted by reading and understanding the contents of regulations, implementation guidelines, teaching modules, and socialization materials directly related to the curriculum policy. The data was analyzed using content analysis techniques to identify the content of the policy, objectives, implementation direction, and challenges faced in the implementation in Islamic-based educational institutions. The results of the document review indicate that implementation challenges remain significant, including: gaps in teachers' understanding of the philosophy and technical aspects of implementing the curriculum, limitations in infrastructure and technology required to support project-based learning, and uneven readiness of teaching tools and educational resources across all madrases. The implications of these findings suggest that strengthening teacher capacity, providing relevant teaching tools, and involving parents and the community are key to creating a responsive, transformative, and meaningful Islamic educational ecosystem for students.